Pembimbingan dan Pendampingan Usaha Mikro dalam Meningkatkan Produktivitas - Danang Dwi Prasetyo; Sholikhah, Asa (MUJAHADA: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service research is to enhance the productivity of micro-businesses in Sumberharjo Village, Sleman, Yogyakarta, through mentoring and assistance in business management, marketing, and financial management. The community service method employed includes training, workshops, and direct mentoring to micro-business owners. This program focuses on improving the participants' ability to manage finances, develop products, and utilize technology for marketing. The results of this community service show significant improvements in micro-business management, as evidenced by the participants’ ability to optimize operations and expand their marketing networks. The impact of the program is also observed in the sustainability of micro-businesses, as the owners are able to maintain business stability and better face market challenges. The implication of this program is that effective mentoring and assistance can strengthen the competitiveness and sustainability of micro-businesses at the local level